The Role of the Digital Reading Corner (POCADI) in Fostering Public Interest in Reading in the Reading Corner of the Astaka Pulpit Ex MTQ Merdeka Square, Tebing Tinggi - Sari, Intan; Siregar, Yusra Dewi; Yusniah (International Journal of Cultural and Social Science, 2022)
This study aims to determine the role of POCADI (Digital Reading Corner) in Fostering Community Reading Interest in the Astaka Eqs Mtq Tebing-High Corner Pulpit, the efforts made to foster reading interest and the obstacles experienced by POCADI (digital reading corner).The the method used in this study is a qualitative method using a descriptive approach. A qualitative method with a descriptive approach as a research procedure that produces descriptive data in the form of written or spoken words from the people or behavior observed, while the data collection techniques used in this study were observation, interviews and documentation. The results of this study indicates that the efforts made by the Digital Reading Corner consist of collaborating with schools, improving facilities and infrastructure, promoting and socializing.